Mercurial > hg > Members > atton > delta_monad
comparison agda/delta.agda @ 80:fc5cd8c50312 InfiniteDelta
Adjust proofs
author | Yasutaka Higa <e115763@ie.u-ryukyu.ac.jp> |
---|---|
date | Mon, 01 Dec 2014 17:30:49 +0900 |
parents | 7307e43a3c76 |
children | 6789c65a75bc |
comparison
equal
deleted
inserted
replaced
79:7307e43a3c76 | 80:fc5cd8c50312 |
---|---|
102 tailDelta (n-tail n (mono x)) ≡⟨ refl ⟩ | 102 tailDelta (n-tail n (mono x)) ≡⟨ refl ⟩ |
103 tailDelta (n-tail n (mono x)) ≡⟨ cong (\t -> tailDelta t) (tail-delta-to-mono n x) ⟩ | 103 tailDelta (n-tail n (mono x)) ≡⟨ cong (\t -> tailDelta t) (tail-delta-to-mono n x) ⟩ |
104 tailDelta (mono x) ≡⟨ refl ⟩ | 104 tailDelta (mono x) ≡⟨ refl ⟩ |
105 mono x ∎ | 105 mono x ∎ |
106 | 106 |
107 head-delta-natural-transformation : {l ll : Level} {A : Set l} {B : Set ll} | 107 head-delta-natural-transformation : {l ll : Level} {A : Set l} {B : Set ll} |
108 -> (f : A -> B) -> (d : Delta A) -> headDelta (fmap f d) ≡ f (headDelta d) | 108 -> (f : A -> B) -> (d : Delta A) -> headDelta (fmap f d) ≡ f (headDelta d) |
109 head-delta-natural-transformation f (mono x) = refl | 109 head-delta-natural-transformation f (mono x) = refl |
110 head-delta-natural-transformation f (delta x d) = refl | 110 head-delta-natural-transformation f (delta x d) = refl |
111 | 111 |
112 n-tail-natural-transformation : {l ll : Level} {A : Set l} {B : Set ll} | 112 n-tail-natural-transformation : {l ll : Level} {A : Set l} {B : Set ll} |
113 -> (n : Nat) -> (f : A -> B) -> (d : Delta A) -> n-tail n (fmap f d) ≡ fmap f (n-tail n d) | 113 -> (n : Nat) -> (f : A -> B) -> (d : Delta A) -> n-tail n (fmap f d) ≡ fmap f (n-tail n d) |
114 n-tail-natural-transformation O f d = refl | 114 n-tail-natural-transformation O f d = refl |
115 n-tail-natural-transformation (S n) f (mono x) = begin | 115 n-tail-natural-transformation (S n) f (mono x) = begin |
144 functor-law-2 f g (mono x) = refl | 144 functor-law-2 f g (mono x) = refl |
145 functor-law-2 f g (delta x d) = cong (delta (f (g x))) (functor-law-2 f g d) | 145 functor-law-2 f g (delta x d) = cong (delta (f (g x))) (functor-law-2 f g d) |
146 | 146 |
147 | 147 |
148 -- Monad-laws (Category) | 148 -- Monad-laws (Category) |
149 {- | |
150 | 149 |
151 monad-law-1-5 : {l : Level} {A : Set l} -> (m : Nat) (n : Nat) -> (ds : Delta (Delta A)) -> | 150 monad-law-1-5 : {l : Level} {A : Set l} -> (m : Nat) (n : Nat) -> (ds : Delta (Delta A)) -> |
152 n-tail n (bind ds (n-tail m)) ≡ bind (n-tail n ds) (n-tail (m + n)) | 151 n-tail n (bind ds (n-tail m)) ≡ bind (n-tail n ds) (n-tail (m + n)) |
153 monad-law-1-5 O O ds = refl | 152 monad-law-1-5 O O ds = refl |
154 monad-law-1-5 O (S n) (mono ds) = begin | 153 monad-law-1-5 O (S n) (mono ds) = begin |
155 n-tail (S n) (bind (mono ds) (n-tail O)) ≡⟨ refl ⟩ | 154 n-tail (S n) (bind (mono ds) (n-tail O)) ≡⟨ refl ⟩ |
156 n-tail (S n) ds ≡⟨ refl ⟩ | 155 n-tail (S n) ds ≡⟨ refl ⟩ |
157 bind (mono ds) (n-tail (S n)) ≡⟨ cong (\de -> bind de (n-tail (S n))) (sym (tail-delta-to-mono (S n) ds)) ⟩ | 156 bind (mono ds) (n-tail (S n)) ≡⟨ cong (\de -> bind de (n-tail (S n))) (sym (tail-delta-to-mono (S n) ds)) ⟩ |
158 bind (n-tail (S n) (mono ds)) (n-tail (S n)) ≡⟨ refl ⟩ | 157 bind (n-tail (S n) (mono ds)) (n-tail (S n)) ≡⟨ refl ⟩ |
159 bind (n-tail (S n) (mono ds)) (n-tail (O + S n)) | 158 bind (n-tail (S n) (mono ds)) (n-tail (O + S n)) |
160 ∎ | 159 ∎ |
161 monad-law-1-5 O (S n) (delta d ds) = begin | 160 monad-law-1-5 O (S n) (delta d ds) = begin |
162 n-tail (S n) (bind (delta d ds) (n-tail O)) ≡⟨ refl ⟩ | 161 n-tail (S n) (bind (delta d ds) (n-tail O)) ≡⟨ refl ⟩ |
163 n-tail (S n) (delta (headDelta d) (bind ds tailDelta )) ≡⟨ cong (\t -> t (delta (headDelta d) (bind ds tailDelta ))) (sym (n-tail-plus n)) ⟩ | 162 n-tail (S n) (delta (headDelta d) (bind ds tailDelta )) ≡⟨ cong (\t -> t (delta (headDelta d) (bind ds tailDelta ))) (sym (n-tail-plus n)) ⟩ |
164 ((n-tail n) ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta )) ≡⟨ refl ⟩ | 163 ((n-tail n) ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta )) ≡⟨ refl ⟩ |
165 (n-tail n) (bind ds tailDelta) ≡⟨ monad-law-1-5 (S O) n ds ⟩ | 164 (n-tail n) (bind ds tailDelta) ≡⟨ monad-law-1-5 (S O) n ds ⟩ |
166 bind (n-tail n ds) (n-tail (S n)) ≡⟨ refl ⟩ | 165 bind (n-tail n ds) (n-tail (S n)) ≡⟨ refl ⟩ |
167 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S n)) ≡⟨ cong (\t -> bind (t (delta d ds)) (n-tail (S n))) (n-tail-plus n) ⟩ | 166 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S n)) ≡⟨ cong (\t -> bind (t (delta d ds)) (n-tail (S n))) (n-tail-plus n) ⟩ |
168 bind (n-tail (S n) (delta d ds)) (n-tail (S n)) ≡⟨ refl ⟩ | 167 bind (n-tail (S n) (delta d ds)) (n-tail (S n)) ≡⟨ refl ⟩ |
169 bind (n-tail (S n) (delta d ds)) (n-tail (O + S n)) | 168 bind (n-tail (S n) (delta d ds)) (n-tail (O + S n)) |
170 ∎ | 169 ∎ |
171 monad-law-1-5 (S m) n (mono (mono x)) = begin | 170 monad-law-1-5 (S m) n (mono (mono x)) = begin |
172 n-tail n (bind (mono (mono x)) (n-tail (S m))) ≡⟨ refl ⟩ | 171 n-tail n (bind (mono (mono x)) (n-tail (S m))) ≡⟨ refl ⟩ |
173 n-tail n (n-tail (S m) (mono x)) ≡⟨ cong (\de -> n-tail n de) (tail-delta-to-mono (S m) x)⟩ | 172 n-tail n (n-tail (S m) (mono x)) ≡⟨ cong (\de -> n-tail n de) (tail-delta-to-mono (S m) x)⟩ |
174 n-tail n (mono x) ≡⟨ tail-delta-to-mono n x ⟩ | 173 n-tail n (mono x) ≡⟨ tail-delta-to-mono n x ⟩ |
175 mono x ≡⟨ sym (tail-delta-to-mono (S m + n) x) ⟩ | 174 mono x ≡⟨ sym (tail-delta-to-mono (S m + n) x) ⟩ |
176 (n-tail (S m + n)) (mono x) ≡⟨ refl ⟩ | 175 (n-tail (S m + n)) (mono x) ≡⟨ refl ⟩ |
177 bind (mono (mono x)) (n-tail (S m + n)) ≡⟨ cong (\de -> bind de (n-tail (S m + n))) (sym (tail-delta-to-mono n (mono x))) ⟩ | 176 bind (mono (mono x)) (n-tail (S m + n)) ≡⟨ cong (\de -> bind de (n-tail (S m + n))) (sym (tail-delta-to-mono n (mono x))) ⟩ |
178 bind (n-tail n (mono (mono x))) (n-tail (S m + n)) | 177 bind (n-tail n (mono (mono x))) (n-tail (S m + n)) |
179 ∎ | 178 ∎ |
180 monad-law-1-5 (S m) n (mono (delta x ds)) = begin | 179 monad-law-1-5 (S m) n (mono (delta x ds)) = begin |
181 n-tail n (bind (mono (delta x ds)) (n-tail (S m))) ≡⟨ refl ⟩ | 180 n-tail n (bind (mono (delta x ds)) (n-tail (S m))) ≡⟨ refl ⟩ |
182 n-tail n (n-tail (S m) (delta x ds)) ≡⟨ cong (\t -> n-tail n (t (delta x ds))) (sym (n-tail-plus m)) ⟩ | 181 n-tail n (n-tail (S m) (delta x ds)) ≡⟨ cong (\t -> n-tail n (t (delta x ds))) (sym (n-tail-plus m)) ⟩ |
183 n-tail n (((n-tail m) ∙ tailDelta) (delta x ds)) ≡⟨ refl ⟩ | 182 n-tail n (((n-tail m) ∙ tailDelta) (delta x ds)) ≡⟨ refl ⟩ |
184 n-tail n ((n-tail m) ds) ≡⟨ cong (\t -> t ds) (n-tail-add {d = ds} n m) ⟩ | 183 n-tail n ((n-tail m) ds) ≡⟨ cong (\t -> t ds) (n-tail-add {d = ds} n m) ⟩ |
185 n-tail (n + m) ds ≡⟨ cong (\n -> n-tail n ds) (nat-add-sym n m) ⟩ | 184 n-tail (n + m) ds ≡⟨ cong (\n -> n-tail n ds) (nat-add-sym n m) ⟩ |
186 n-tail (m + n) ds ≡⟨ refl ⟩ | 185 n-tail (m + n) ds ≡⟨ refl ⟩ |
187 ((n-tail (m + n)) ∙ tailDelta) (delta x ds) ≡⟨ cong (\t -> t (delta x ds)) (n-tail-plus (m + n))⟩ | 186 ((n-tail (m + n)) ∙ tailDelta) (delta x ds) ≡⟨ cong (\t -> t (delta x ds)) (n-tail-plus (m + n))⟩ |
188 n-tail (S (m + n)) (delta x ds) ≡⟨ refl ⟩ | 187 n-tail (S (m + n)) (delta x ds) ≡⟨ refl ⟩ |
189 n-tail (S m + n) (delta x ds) ≡⟨ refl ⟩ | 188 n-tail (S m + n) (delta x ds) ≡⟨ refl ⟩ |
190 bind (mono (delta x ds)) (n-tail (S m + n)) ≡⟨ cong (\de -> bind de (n-tail (S m + n))) (sym (tail-delta-to-mono n (delta x ds))) ⟩ | 189 bind (mono (delta x ds)) (n-tail (S m + n)) ≡⟨ cong (\de -> bind de (n-tail (S m + n))) (sym (tail-delta-to-mono n (delta x ds))) ⟩ |
191 bind (n-tail n (mono (delta x ds))) (n-tail (S m + n)) | 190 bind (n-tail n (mono (delta x ds))) (n-tail (S m + n)) |
192 ∎ | 191 ∎ |
193 monad-law-1-5 (S m) O (delta d ds) = begin | 192 monad-law-1-5 (S m) O (delta d ds) = begin |
194 n-tail O (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ | 193 n-tail O (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ |
195 (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ | 194 (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ |
196 delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m)))) ≡⟨ refl ⟩ | 195 delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m)))) ≡⟨ refl ⟩ |
197 bind (delta d ds) (n-tail (S m)) ≡⟨ refl ⟩ | 196 bind (delta d ds) (n-tail (S m)) ≡⟨ refl ⟩ |
198 bind (n-tail O (delta d ds)) (n-tail (S m)) ≡⟨ cong (\n -> bind (n-tail O (delta d ds)) (n-tail n)) (nat-add-right-zero (S m)) ⟩ | 197 bind (n-tail O (delta d ds)) (n-tail (S m)) ≡⟨ cong (\n -> bind (n-tail O (delta d ds)) (n-tail n)) (nat-add-right-zero (S m)) ⟩ |
199 bind (n-tail O (delta d ds)) (n-tail (S m + O)) | 198 bind (n-tail O (delta d ds)) (n-tail (S m + O)) |
200 ∎ | 199 ∎ |
201 monad-law-1-5 (S m) (S n) (delta d ds) = begin | 200 monad-law-1-5 (S m) (S n) (delta d ds) = begin |
202 n-tail (S n) (bind (delta d ds) (n-tail (S m))) ≡⟨ cong (\t -> t ((bind (delta d ds) (n-tail (S m))))) (sym (n-tail-plus n)) ⟩ | 201 n-tail (S n) (bind (delta d ds) (n-tail (S m))) ≡⟨ cong (\t -> t ((bind (delta d ds) (n-tail (S m))))) (sym (n-tail-plus n)) ⟩ |
203 ((n-tail n) ∙ tailDelta) (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ | 202 ((n-tail n) ∙ tailDelta) (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ |
204 ((n-tail n) ∙ tailDelta) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ | 203 ((n-tail n) ∙ tailDelta) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ |
205 (n-tail n) (bind ds (tailDelta ∙ (n-tail (S m)))) ≡⟨ refl ⟩ | 204 (n-tail n) (bind ds (tailDelta ∙ (n-tail (S m)))) ≡⟨ refl ⟩ |
206 (n-tail n) (bind ds (n-tail (S (S m)))) ≡⟨ monad-law-1-5 (S (S m)) n ds ⟩ | 205 (n-tail n) (bind ds (n-tail (S (S m)))) ≡⟨ monad-law-1-5 (S (S m)) n ds ⟩ |
207 bind ((n-tail n) ds) (n-tail (S (S (m + n)))) ≡⟨ cong (\nm -> bind ((n-tail n) ds) (n-tail nm)) (sym (nat-right-increment (S m) n)) ⟩ | 206 bind ((n-tail n) ds) (n-tail (S (S (m + n)))) ≡⟨ cong (\nm -> bind ((n-tail n) ds) (n-tail nm)) (sym (nat-right-increment (S m) n)) ⟩ |
208 bind ((n-tail n) ds) (n-tail (S m + S n)) ≡⟨ refl ⟩ | 207 bind ((n-tail n) ds) (n-tail (S m + S n)) ≡⟨ refl ⟩ |
209 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S m + S n)) ≡⟨ cong (\t -> bind (t (delta d ds)) (n-tail (S m + S n))) (n-tail-plus n) ⟩ | 208 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S m + S n)) ≡⟨ cong (\t -> bind (t (delta d ds)) (n-tail (S m + S n))) (n-tail-plus n) ⟩ |
210 bind (n-tail (S n) (delta d ds)) (n-tail (S m + S n)) | 209 bind (n-tail (S n) (delta d ds)) (n-tail (S m + S n)) |
211 ∎ | 210 ∎ |
212 | 211 |
213 monad-law-1-4 : {l : Level} {A : Set l} -> (m n : Nat) -> (dd : Delta (Delta A)) -> | 212 monad-law-1-4 : {l : Level} {A : Set l} -> (m n : Nat) -> (dd : Delta (Delta A)) -> |
214 headDelta ((n-tail n) (bind dd (n-tail m))) ≡ headDelta ((n-tail (m + n)) (headDelta (n-tail n dd))) | 213 headDelta ((n-tail n) (bind dd (n-tail m))) ≡ headDelta ((n-tail (m + n)) (headDelta (n-tail n dd))) |
215 monad-law-1-4 O O (mono dd) = refl | 214 monad-law-1-4 O O (mono dd) = refl |
216 monad-law-1-4 O O (delta dd dd₁) = refl | 215 monad-law-1-4 O O (delta dd dd₁) = refl |
217 monad-law-1-4 O (S n) (mono dd) = begin | 216 monad-law-1-4 O (S n) (mono dd) = begin |
218 headDelta (n-tail (S n) (bind (mono dd) (n-tail O))) ≡⟨ refl ⟩ | 217 headDelta (n-tail (S n) (bind (mono dd) (n-tail O))) ≡⟨ refl ⟩ |
219 headDelta (n-tail (S n) dd) ≡⟨ refl ⟩ | 218 headDelta (n-tail (S n) dd) ≡⟨ refl ⟩ |
220 headDelta (n-tail (S n) (headDelta (mono dd))) ≡⟨ cong (\de -> headDelta (n-tail (S n) (headDelta de))) (sym (tail-delta-to-mono (S n) dd)) ⟩ | 219 headDelta (n-tail (S n) (headDelta (mono dd))) ≡⟨ cong (\de -> headDelta (n-tail (S n) (headDelta de))) (sym (tail-delta-to-mono (S n) dd)) ⟩ |
221 headDelta (n-tail (S n) (headDelta (n-tail (S n) (mono dd)))) ≡⟨ refl ⟩ | 220 headDelta (n-tail (S n) (headDelta (n-tail (S n) (mono dd)))) ≡⟨ refl ⟩ |
222 headDelta (n-tail (O + S n) (headDelta (n-tail (S n) (mono dd)))) | 221 headDelta (n-tail (O + S n) (headDelta (n-tail (S n) (mono dd)))) |
223 ∎ | 222 ∎ |
224 monad-law-1-4 O (S n) (delta d ds) = begin | 223 monad-law-1-4 O (S n) (delta d ds) = begin |
225 headDelta (n-tail (S n) (bind (delta d ds) (n-tail O))) ≡⟨ refl ⟩ | 224 headDelta (n-tail (S n) (bind (delta d ds) (n-tail O))) ≡⟨ refl ⟩ |
226 headDelta (n-tail (S n) (bind (delta d ds) id)) ≡⟨ refl ⟩ | 225 headDelta (n-tail (S n) (bind (delta d ds) id)) ≡⟨ refl ⟩ |
227 headDelta (n-tail (S n) (delta (headDelta d) (bind ds tailDelta))) ≡⟨ cong (\t -> headDelta (t (delta (headDelta d) (bind ds tailDelta)))) (sym (n-tail-plus n)) ⟩ | 226 headDelta (n-tail (S n) (delta (headDelta d) (bind ds tailDelta))) ≡⟨ cong (\t -> headDelta (t (delta (headDelta d) (bind ds tailDelta)))) (sym (n-tail-plus n)) ⟩ |
228 headDelta (((n-tail n) ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta))) ≡⟨ refl ⟩ | 227 headDelta (((n-tail n) ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta))) ≡⟨ refl ⟩ |
229 headDelta (n-tail n (bind ds tailDelta)) ≡⟨ monad-law-1-4 (S O) n ds ⟩ | 228 headDelta (n-tail n (bind ds tailDelta)) ≡⟨ monad-law-1-4 (S O) n ds ⟩ |
230 headDelta (n-tail (S n) (headDelta (n-tail n ds))) ≡⟨ refl ⟩ | 229 headDelta (n-tail (S n) (headDelta (n-tail n ds))) ≡⟨ refl ⟩ |
231 headDelta (n-tail (S n) (headDelta (((n-tail n) ∙ tailDelta) (delta d ds)))) ≡⟨ cong (\t -> headDelta (n-tail (S n) (headDelta (t (delta d ds))))) (n-tail-plus n) ⟩ | 230 headDelta (n-tail (S n) (headDelta (((n-tail n) ∙ tailDelta) (delta d ds)))) ≡⟨ cong (\t -> headDelta (n-tail (S n) (headDelta (t (delta d ds))))) (n-tail-plus n) ⟩ |
232 headDelta (n-tail (S n) (headDelta (n-tail (S n) (delta d ds)))) ≡⟨ refl ⟩ | 231 headDelta (n-tail (S n) (headDelta (n-tail (S n) (delta d ds)))) ≡⟨ refl ⟩ |
233 headDelta (n-tail (O + S n) (headDelta (n-tail (S n) (delta d ds)))) | 232 headDelta (n-tail (O + S n) (headDelta (n-tail (S n) (delta d ds)))) |
234 ∎ | 233 ∎ |
235 monad-law-1-4 (S m) n (mono dd) = begin | 234 monad-law-1-4 (S m) n (mono dd) = begin |
236 headDelta (n-tail n (bind (mono dd) (n-tail (S m)))) ≡⟨ refl ⟩ | 235 headDelta (n-tail n (bind (mono dd) (n-tail (S m)))) ≡⟨ refl ⟩ |
237 headDelta (n-tail n ((n-tail (S m)) dd))≡⟨ cong (\t -> headDelta (t dd)) (n-tail-add {d = dd} n (S m)) ⟩ | 236 headDelta (n-tail n ((n-tail (S m)) dd)) ≡⟨ cong (\t -> headDelta (t dd)) (n-tail-add {d = dd} n (S m)) ⟩ |
238 headDelta (n-tail (n + S m) dd) ≡⟨ cong (\n -> headDelta ((n-tail n) dd)) (nat-add-sym n (S m)) ⟩ | 237 headDelta (n-tail (n + S m) dd) ≡⟨ cong (\n -> headDelta ((n-tail n) dd)) (nat-add-sym n (S m)) ⟩ |
239 headDelta (n-tail (S m + n) dd) ≡⟨ refl ⟩ | 238 headDelta (n-tail (S m + n) dd) ≡⟨ refl ⟩ |
240 headDelta (n-tail (S m + n) (headDelta (mono dd))) ≡⟨ cong (\de -> headDelta (n-tail (S m + n) (headDelta de))) (sym (tail-delta-to-mono n dd)) ⟩ | 239 headDelta (n-tail (S m + n) (headDelta (mono dd))) ≡⟨ cong (\de -> headDelta (n-tail (S m + n) (headDelta de))) (sym (tail-delta-to-mono n dd)) ⟩ |
241 headDelta (n-tail (S m + n) (headDelta (n-tail n (mono dd)))) | 240 headDelta (n-tail (S m + n) (headDelta (n-tail n (mono dd)))) |
242 ∎ | 241 ∎ |
243 monad-law-1-4 (S m) O (delta d ds) = begin | 242 monad-law-1-4 (S m) O (delta d ds) = begin |
244 headDelta (n-tail O (bind (delta d ds) (n-tail (S m)))) ≡⟨ refl ⟩ | 243 headDelta (n-tail O (bind (delta d ds) (n-tail (S m)))) ≡⟨ refl ⟩ |
245 headDelta (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ | 244 headDelta (bind (delta d ds) (n-tail (S m))) ≡⟨ refl ⟩ |
246 headDelta (delta (headDelta ((n-tail (S m) d))) (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ | 245 headDelta (delta (headDelta ((n-tail (S m) d))) (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ |
247 headDelta (n-tail (S m) d) ≡⟨ cong (\n -> headDelta ((n-tail n) d)) (nat-add-right-zero (S m)) ⟩ | 246 headDelta (n-tail (S m) d) ≡⟨ cong (\n -> headDelta ((n-tail n) d)) (nat-add-right-zero (S m)) ⟩ |
248 headDelta (n-tail (S m + O) d) ≡⟨ refl ⟩ | 247 headDelta (n-tail (S m + O) d) ≡⟨ refl ⟩ |
249 headDelta (n-tail (S m + O) (headDelta (delta d ds))) ≡⟨ refl ⟩ | 248 headDelta (n-tail (S m + O) (headDelta (delta d ds))) ≡⟨ refl ⟩ |
250 headDelta (n-tail (S m + O) (headDelta (n-tail O (delta d ds)))) | 249 headDelta (n-tail (S m + O) (headDelta (n-tail O (delta d ds)))) |
251 ∎ | 250 ∎ |
252 monad-law-1-4 (S m) (S n) (delta d ds) = begin | 251 monad-law-1-4 (S m) (S n) (delta d ds) = begin |
253 headDelta (n-tail (S n) (bind (delta d ds) (n-tail (S m)))) ≡⟨ refl ⟩ | 252 headDelta (n-tail (S n) (bind (delta d ds) (n-tail (S m)))) ≡⟨ refl ⟩ |
254 headDelta (n-tail (S n) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m)))))) ≡⟨ cong (\t -> headDelta (t (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))))) (sym (n-tail-plus n)) ⟩ | 253 headDelta (n-tail (S n) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m)))))) ≡⟨ cong (\t -> headDelta (t (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))))) (sym (n-tail-plus n)) ⟩ |
255 headDelta ((((n-tail n) ∙ tailDelta) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))))) ≡⟨ refl ⟩ | 254 headDelta ((((n-tail n) ∙ tailDelta) (delta (headDelta ((n-tail (S m)) d)) (bind ds (tailDelta ∙ (n-tail (S m))))))) ≡⟨ refl ⟩ |
256 headDelta (n-tail n (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ | 255 headDelta (n-tail n (bind ds (tailDelta ∙ (n-tail (S m))))) ≡⟨ refl ⟩ |
257 headDelta (n-tail n (bind ds (n-tail (S (S m))))) ≡⟨ monad-law-1-4 (S (S m)) n ds ⟩ | 256 headDelta (n-tail n (bind ds (n-tail (S (S m))))) ≡⟨ monad-law-1-4 (S (S m)) n ds ⟩ |
258 headDelta (n-tail ((S (S m) + n)) (headDelta (n-tail n ds))) ≡⟨ cong (\nm -> headDelta ((n-tail nm) (headDelta (n-tail n ds)))) (sym (nat-right-increment (S m) n)) ⟩ | 257 headDelta (n-tail ((S (S m) + n)) (headDelta (n-tail n ds))) ≡⟨ cong (\nm -> headDelta ((n-tail nm) (headDelta (n-tail n ds)))) (sym (nat-right-increment (S m) n)) ⟩ |
259 headDelta (n-tail (S m + S n) (headDelta (n-tail n ds))) ≡⟨ refl ⟩ | 258 headDelta (n-tail (S m + S n) (headDelta (n-tail n ds))) ≡⟨ refl ⟩ |
260 headDelta (n-tail (S m + S n) (headDelta (((n-tail n) ∙ tailDelta) (delta d ds)))) ≡⟨ cong (\t -> headDelta (n-tail (S m + S n) (headDelta (t (delta d ds))))) (n-tail-plus n) ⟩ | 259 headDelta (n-tail (S m + S n) (headDelta (((n-tail n) ∙ tailDelta) (delta d ds)))) ≡⟨ cong (\t -> headDelta (n-tail (S m + S n) (headDelta (t (delta d ds))))) (n-tail-plus n) ⟩ |
261 headDelta (n-tail (S m + S n) (headDelta (n-tail (S n) (delta d ds)))) | 260 headDelta (n-tail (S m + S n) (headDelta (n-tail (S n) (delta d ds)))) |
262 ∎ | 261 ∎ |
263 | 262 |
264 monad-law-1-2 : {l : Level} {A : Set l} -> (d : Delta (Delta A)) -> headDelta (mu d) ≡ (headDelta (headDelta d)) | 263 monad-law-1-2 : {l : Level} {A : Set l} -> (d : Delta (Delta A)) -> headDelta (mu d) ≡ (headDelta (headDelta d)) |
265 monad-law-1-2 (mono _) = refl | 264 monad-law-1-2 (mono _) = refl |
267 | 266 |
268 monad-law-1-3 : {l : Level} {A : Set l} -> (n : Nat) -> (d : Delta (Delta (Delta A))) -> | 267 monad-law-1-3 : {l : Level} {A : Set l} -> (n : Nat) -> (d : Delta (Delta (Delta A))) -> |
269 bind (fmap mu d) (n-tail n) ≡ bind (bind d (n-tail n)) (n-tail n) | 268 bind (fmap mu d) (n-tail n) ≡ bind (bind d (n-tail n)) (n-tail n) |
270 monad-law-1-3 O (mono d) = refl | 269 monad-law-1-3 O (mono d) = refl |
271 monad-law-1-3 O (delta d ds) = begin | 270 monad-law-1-3 O (delta d ds) = begin |
272 bind (fmap mu (delta d ds)) (n-tail O) ≡⟨ refl ⟩ | 271 bind (fmap mu (delta d ds)) (n-tail O) ≡⟨ refl ⟩ |
273 bind (delta (mu d) (fmap mu ds)) (n-tail O) ≡⟨ refl ⟩ | 272 bind (delta (mu d) (fmap mu ds)) (n-tail O) ≡⟨ refl ⟩ |
274 delta (headDelta (mu d)) (bind (fmap mu ds) tailDelta) ≡⟨ cong (\dx -> delta dx (bind (fmap mu ds) tailDelta)) (monad-law-1-2 d) ⟩ | 273 delta (headDelta (mu d)) (bind (fmap mu ds) tailDelta) ≡⟨ cong (\dx -> delta dx (bind (fmap mu ds) tailDelta)) (monad-law-1-2 d) ⟩ |
275 delta (headDelta (headDelta d)) (bind (fmap mu ds) tailDelta) ≡⟨ cong (\dx -> delta (headDelta (headDelta d)) dx) (monad-law-1-3 (S O) ds) ⟩ | 274 delta (headDelta (headDelta d)) (bind (fmap mu ds) tailDelta) ≡⟨ cong (\dx -> delta (headDelta (headDelta d)) dx) (monad-law-1-3 (S O) ds) ⟩ |
276 delta (headDelta (headDelta d)) (bind (bind ds tailDelta) tailDelta) ≡⟨ refl ⟩ | 275 delta (headDelta (headDelta d)) (bind (bind ds tailDelta) tailDelta) ≡⟨ refl ⟩ |
277 bind (delta (headDelta d) (bind ds tailDelta)) (n-tail O) ≡⟨ refl ⟩ | 276 bind (delta (headDelta d) (bind ds tailDelta)) (n-tail O) ≡⟨ refl ⟩ |
278 bind (bind (delta d ds) (n-tail O)) (n-tail O) | 277 bind (bind (delta d ds) (n-tail O)) (n-tail O) |
279 ∎ | 278 ∎ |
280 monad-law-1-3 (S n) (mono (mono d)) = begin | 279 monad-law-1-3 (S n) (mono (mono d)) = begin |
281 bind (fmap mu (mono (mono d))) (n-tail (S n)) ≡⟨ refl ⟩ | 280 bind (fmap mu (mono (mono d))) (n-tail (S n)) ≡⟨ refl ⟩ |
282 bind (mono d) (n-tail (S n)) ≡⟨ refl ⟩ | 281 bind (mono d) (n-tail (S n)) ≡⟨ refl ⟩ |
283 (n-tail (S n)) d ≡⟨ refl ⟩ | 282 (n-tail (S n)) d ≡⟨ refl ⟩ |
284 bind (mono d) (n-tail (S n)) ≡⟨ cong (\t -> bind t (n-tail (S n))) (sym (tail-delta-to-mono (S n) d))⟩ | 283 bind (mono d) (n-tail (S n)) ≡⟨ cong (\t -> bind t (n-tail (S n))) (sym (tail-delta-to-mono (S n) d))⟩ |
285 bind (n-tail (S n) (mono d)) (n-tail (S n)) ≡⟨ refl ⟩ | 284 bind (n-tail (S n) (mono d)) (n-tail (S n)) ≡⟨ refl ⟩ |
286 bind (n-tail (S n) (mono d)) (n-tail (S n)) ≡⟨ refl ⟩ | 285 bind (n-tail (S n) (mono d)) (n-tail (S n)) ≡⟨ refl ⟩ |
287 bind (bind (mono (mono d)) (n-tail (S n))) (n-tail (S n)) | 286 bind (bind (mono (mono d)) (n-tail (S n))) (n-tail (S n)) |
288 ∎ | 287 ∎ |
289 monad-law-1-3 (S n) (mono (delta d ds)) = begin | 288 monad-law-1-3 (S n) (mono (delta d ds)) = begin |
290 bind (fmap mu (mono (delta d ds))) (n-tail (S n)) ≡⟨ refl ⟩ | 289 bind (fmap mu (mono (delta d ds))) (n-tail (S n)) ≡⟨ refl ⟩ |
291 bind (mono (mu (delta d ds))) (n-tail (S n)) ≡⟨ refl ⟩ | 290 bind (mono (mu (delta d ds))) (n-tail (S n)) ≡⟨ refl ⟩ |
292 n-tail (S n) (mu (delta d ds)) ≡⟨ refl ⟩ | 291 n-tail (S n) (mu (delta d ds)) ≡⟨ refl ⟩ |
293 n-tail (S n) (delta (headDelta d) (bind ds tailDelta)) ≡⟨ cong (\t -> t (delta (headDelta d) (bind ds tailDelta))) (sym (n-tail-plus n)) ⟩ | 292 n-tail (S n) (delta (headDelta d) (bind ds tailDelta)) ≡⟨ cong (\t -> t (delta (headDelta d) (bind ds tailDelta))) (sym (n-tail-plus n)) ⟩ |
294 (n-tail n ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta)) ≡⟨ refl ⟩ | 293 (n-tail n ∙ tailDelta) (delta (headDelta d) (bind ds tailDelta)) ≡⟨ refl ⟩ |
295 n-tail n (bind ds tailDelta) ≡⟨ monad-law-1-5 (S O) n ds ⟩ | 294 n-tail n (bind ds tailDelta) ≡⟨ monad-law-1-5 (S O) n ds ⟩ |
296 bind (n-tail n ds) (n-tail (S n)) ≡⟨ refl ⟩ | 295 bind (n-tail n ds) (n-tail (S n)) ≡⟨ refl ⟩ |
297 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S n)) ≡⟨ cong (\t -> (bind (t (delta d ds)) (n-tail (S n)))) (n-tail-plus n) ⟩ | 296 bind (((n-tail n) ∙ tailDelta) (delta d ds)) (n-tail (S n)) ≡⟨ cong (\t -> (bind (t (delta d ds)) (n-tail (S n)))) (n-tail-plus n) ⟩ |
298 bind (n-tail (S n) (delta d ds)) (n-tail (S n)) ≡⟨ refl ⟩ | 297 bind (n-tail (S n) (delta d ds)) (n-tail (S n)) ≡⟨ refl ⟩ |
299 bind (bind (mono (delta d ds)) (n-tail (S n))) (n-tail (S n)) | 298 bind (bind (mono (delta d ds)) (n-tail (S n))) (n-tail (S n)) |
300 ∎ | 299 ∎ |
301 monad-law-1-3 (S n) (delta (mono d) ds) = begin | 300 monad-law-1-3 (S n) (delta (mono d) ds) = begin |
302 bind (fmap mu (delta (mono d) ds)) (n-tail (S n)) ≡⟨ refl ⟩ | 301 bind (fmap mu (delta (mono d) ds)) (n-tail (S n)) ≡⟨ refl ⟩ |
303 bind (delta (mu (mono d)) (fmap mu ds)) (n-tail (S n)) ≡⟨ refl ⟩ | 302 bind (delta (mu (mono d)) (fmap mu ds)) (n-tail (S n)) ≡⟨ refl ⟩ |
333 | 332 |
334 -- monad-law-1 : join . fmap join = join . join | 333 -- monad-law-1 : join . fmap join = join . join |
335 monad-law-1 : {l : Level} {A : Set l} -> (d : Delta (Delta (Delta A))) -> ((mu ∙ (fmap mu)) d) ≡ ((mu ∙ mu) d) | 334 monad-law-1 : {l : Level} {A : Set l} -> (d : Delta (Delta (Delta A))) -> ((mu ∙ (fmap mu)) d) ≡ ((mu ∙ mu) d) |
336 monad-law-1 (mono d) = refl | 335 monad-law-1 (mono d) = refl |
337 monad-law-1 (delta x d) = begin | 336 monad-law-1 (delta x d) = begin |
338 (mu ∙ fmap mu) (delta x d) | 337 (mu ∙ fmap mu) (delta x d) ≡⟨ refl ⟩ |
339 ≡⟨ refl ⟩ | 338 mu (fmap mu (delta x d)) ≡⟨ refl ⟩ |
340 mu (fmap mu (delta x d)) | 339 mu (delta (mu x) (fmap mu d)) ≡⟨ refl ⟩ |
341 ≡⟨ refl ⟩ | 340 delta (headDelta (mu x)) (bind (fmap mu d) tailDelta) ≡⟨ cong (\x -> delta x (bind (fmap mu d) tailDelta)) (monad-law-1-2 x) ⟩ |
342 mu (delta (mu x) (fmap mu d)) | 341 delta (headDelta (headDelta x)) (bind (fmap mu d) tailDelta) ≡⟨ cong (\d -> delta (headDelta (headDelta x)) d) (monad-law-1-3 (S O) d) ⟩ |
343 ≡⟨ refl ⟩ | 342 delta (headDelta (headDelta x)) (bind (bind d tailDelta) tailDelta) ≡⟨ refl ⟩ |
344 delta (headDelta (mu x)) (bind (fmap mu d) tailDelta) | 343 mu (delta (headDelta x) (bind d tailDelta)) ≡⟨ refl ⟩ |
345 ≡⟨ cong (\x -> delta x (bind (fmap mu d) tailDelta)) (monad-law-1-2 x) ⟩ | 344 mu (mu (delta x d)) ≡⟨ refl ⟩ |
346 delta (headDelta (headDelta x)) (bind (fmap mu d) tailDelta) | |
347 ≡⟨ cong (\d -> delta (headDelta (headDelta x)) d) (monad-law-1-3 (S O) d) ⟩ | |
348 delta (headDelta (headDelta x)) (bind (bind d tailDelta) tailDelta) | |
349 ≡⟨ refl ⟩ | |
350 mu (delta (headDelta x) (bind d tailDelta)) | |
351 ≡⟨ refl ⟩ | |
352 mu (mu (delta x d)) | |
353 ≡⟨ refl ⟩ | |
354 (mu ∙ mu) (delta x d) | 345 (mu ∙ mu) (delta x d) |
355 ∎ | 346 ∎ |
356 | 347 |
357 | |
358 -} | |
359 | 348 |
360 monad-law-2-1 : {l : Level} {A : Set l} -> (n : Nat) -> (d : Delta A) -> (bind (fmap eta d) (n-tail n)) ≡ d | 349 monad-law-2-1 : {l : Level} {A : Set l} -> (n : Nat) -> (d : Delta A) -> (bind (fmap eta d) (n-tail n)) ≡ d |
361 monad-law-2-1 O (mono x) = refl | 350 monad-law-2-1 O (mono x) = refl |
362 monad-law-2-1 O (delta x d) = begin | 351 monad-law-2-1 O (delta x d) = begin |
363 bind (fmap eta (delta x d)) (n-tail O) ≡⟨ refl ⟩ | 352 bind (fmap eta (delta x d)) (n-tail O) ≡⟨ refl ⟩ |